(untitled) (Citizenship in Action: Extension and Culture Magazine, 2025)
Originating in scientific thought and influenced by the social sciences, scientific communication is today a consolidated field of research that reflects communication between institutions and between the cultures of science and society in general. In view of this, this article proposes to present the Instagram® profile "Enraizando Saberes UPE", built for the purpose of scientific dissemination and university extension.the data presented here is based on the metrics provided by Instagram® and did not involve a direct invitation from the followers of the Enraizando Saberes UPE page, between February 2023 and February 2024, the profile shared 82 publications, 75 of which were posts in the feed and 7 were reels. Totaling 1,484 likes on publications and 117 on reels. In the same period, the project received 239 comments, 295 shares and 67 saves. The profile reached a total of 325 followers in one year of activity. In February 2024, the last month of registration for publication, the profile of the followers was mostly female (56.9%), with a predominant age range of 25 to 34 years (41.1%), followed by 18 to 24 years (29.9%) and 25 (21.8%). The experience of disseminating science through the Enraizando Saberes profile on the Instagram® platform was considered successful by the researchers. The profile managed to transmit information that was previously restricted to academia in a democratic way to the general public.